Tabletop game design for video game designers - Ham, Ethan (Online access with DDA: Askews (Maths), 2016)
Experienced game designer Ethan Ham presents game mechanic design in a step-by-step format that takes the reader from thinking about games to actually making them. His book reaches beyond simple description and definition to explore the issues designers grapple with on every game they create.